Religiosity as a Cultural Resource for Arab-Palestinian Women's Coping with Cancer. (January 2020) - Almuhtaseb, Mona I. A.; Alby, Francesca; Zucchermaglio, Cristina; Fatigante, Marilena
Drawing on the discourse analysis of 36 in-depth interviews, this qualitative study explores how Arab-Palestinian women cope with breast cancer and ascribe meaning to their illness within the local religious and traditional cultural context. In particular, the study shows that religious beliefs and practices help Arab-Palestinian women to handle emotional and psychological difficulties while perpetuating traditional cultural norms of concealment. Two main functions of religiosity as a coping resource are analyzed by (a) managing distress and identity crisis and (b) changing the meaning of the illness experience. In this sociocultural context, the practice of religious rituals provides cancer patients with an effective and culturally situated instrument for coping with a deep existential crisis. Practical implications of the study are discussed in the conclusions.